2011
DOI: 10.1080/19406940.2011.596159
|View full text |Cite
|
Sign up to set email alerts
|

The governance of sport, gender and (dis)ability

Abstract: Drawing on the Foucauldian concept of governmentality and with a discourse analytic approach, the purpose of this study was to describe and analyse how wheelchair basketball (WCB) players governed themselves in relation to the dominant discourses of sport, gender and disability. This study was based on semi-structured interviews with 12 men and 6 women with and without classified impairment. The findings illustrated how governing operates in the micro-context of WCB and how the athletes were constituted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Adams, 2011; Fahlén and Karp, 2010; May et al, 2013; Nichols et al, 2012; O’Gorman, 2011; Skille, 2009; Stenling, 2013). As sport and other voluntary organisations are increasingly being included in policies for welfare provision in a variety of national contexts and depicted as important resources in solving various social problems, many scholars have directed attention to interventions, programmes, projects, and activities targeting a wide range of social objectives such as public health (Thing and Ottesen, 2010), equal opportunity (Wickman, 2011), ethnic integration (Theeboom et al, 2012), social integration (Haudenhuyse et al, 2014), urban regeneration (Coaffee, 2008), democracy (Morgan, 2013), criminality (Mutz and Baur, 2009), youth delinquency (Stenling, 2014), peace (Hasselgård and Straume, 2015), national identity (Grix and Carmichael, 2012), and individual identity (Thorpe, 2014). Taken together, these studies and others have shown how policy implementation in general is contingent on a variety of properties associated with the bodies responsible for issuing the policy in question (Piggin et al, 2009), the cultural raw material of the policy (Stenling and Fahlén, 2014), the implementation process (O’Gorman, 2011), and the organisations expected to implement it (Reid, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Adams, 2011; Fahlén and Karp, 2010; May et al, 2013; Nichols et al, 2012; O’Gorman, 2011; Skille, 2009; Stenling, 2013). As sport and other voluntary organisations are increasingly being included in policies for welfare provision in a variety of national contexts and depicted as important resources in solving various social problems, many scholars have directed attention to interventions, programmes, projects, and activities targeting a wide range of social objectives such as public health (Thing and Ottesen, 2010), equal opportunity (Wickman, 2011), ethnic integration (Theeboom et al, 2012), social integration (Haudenhuyse et al, 2014), urban regeneration (Coaffee, 2008), democracy (Morgan, 2013), criminality (Mutz and Baur, 2009), youth delinquency (Stenling, 2014), peace (Hasselgård and Straume, 2015), national identity (Grix and Carmichael, 2012), and individual identity (Thorpe, 2014). Taken together, these studies and others have shown how policy implementation in general is contingent on a variety of properties associated with the bodies responsible for issuing the policy in question (Piggin et al, 2009), the cultural raw material of the policy (Stenling and Fahlén, 2014), the implementation process (O’Gorman, 2011), and the organisations expected to implement it (Reid, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the sport movement at a strategic level had an ambition to broaden the uptake of members based on the goal to reach public health defined vulnerable groups in society, it is the members at an operative level that determine the actions and activities, and ultimately the target population really being prioritized. Previous studies have shown sport's difficulties in attracting, including and prioritizing minorities and vulnerable groups, and problems in relying on civil society organizations for this (Girginov, 2008;Morgan, 2013;Stenling, 2014;Thorpe, 2014;Wickman, 2011). The challenge for the sports movement is to regard equality, inclusion and equal opportunities to physical activity and health from a population perspective when in fact the member perspective is an obligation.…”
Section: Discussionmentioning
confidence: 99%
“…Although disability sport has grown rapidly and has gained increased attention (Wickman 2011), the factor of being disabled has so far not been intensely investigated in general sport participation studies. It can be assumed that having a disability prevents people from taking part in sports in general due to the physical or mental constitution of the individuals.…”
Section: Individual-level: Socio-economic Indicatorsmentioning
confidence: 99%